Autoregressive Distributed Lag Model Approach on the Effect of Monetary Policy in Nigerian Banking Sector - Bilkisu Maijamaa; Anna Anna Kolade.O (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2021)
A healthy banking system is determined by the amount of money supply which can be monitored through various monetary policy instruments. A lot of study has shown studies from other countries on various monetary policies used with scanty literature as it relates to Nigeria, and this research is aimed at looking at the Nigerian scenario. Method used for this study is empirical on the effect of monetary policy on banking in Nigeria. Time series data from 2004-2019 was used with an autoregressive distributed lag approach and error correction mechanism. The findings from this study are; there is an evidence of significant relationship between the dependent and the explanatory variables with a long-run relationship between credit reserve ratio and money supply on bank loans and advances while other variables such as monetary policy rate (MPR) and liquidity ratio (LQR) are not significant on bank loans and advances in Nigeria. The error correction mechanism reveals the existence of cointegration, stating that there is a long-run relationship among the dependent and the explanatory variables. Structural changes in monetary policy is significant on bank loans hence suggesting a significant effect on bank loans and advances. This research serves as a great relevance to policy makers which implies monetary authorities should review and formulate an efficient policy such as fiscal policy to help boost bank industries in Nigeria